Do Early Fetal Measurements and Nuchal Translucency Correlate With Term Birth Weight? - Hackmon, Rinat; Librach, Clifford; Burwick, Richard; Rodrigues, Nicole; Farine, Dan; Berger, Howard (Journal of obstetrics and gynaecology Canada, 2017)
Traditionally, physiological variation in fetal weight is believed to emerge during the latter half of pregnancy. Although recent evidence suggests that crown-rump length (CRL) and nuchal translucency (NT) measured at 11–14 weeks correlate with abnormal fetal growth, findings have been limited by dating accuracy in spontaneous gestations. Therefore, we sought to determine whether CRL or NT measurements correlated with term birth weight (BW) or BW ratio in a cohort of IVF pregnancies, in which the date of conception is precisely known. This retrospective cohort study included 227 term, singleton IVF pregnancies. Subjects were included if they had an early first-trimester ultrasound examination and subsequent nuchal translucency (NT) screening. The difference between the measured and the expected CRL and the biparietal diameter (BPD) and NT measurement were calculated and correlated with the actual term BW or BW ratio. The BW ratio was calculated using the actual BW and the expected BW for GA. The difference between measured and expected mid–first-trimester CRL, and the BPD at NT assessment, correlated with BW ratio at delivery (rSpearman = 0.15, P = 0.023 and rSpearman = 0.27, P < 0.001, respectively). Absolute NT measurements and NT percentiles (adjusted for CRL) correlated with BW ratio at delivery (rSpearman = 0.18, r = 0.14, and P = 0.005 and 0.038, respectively). In this well-dated IVF population, we report a significant correlation between BW ratio and first-trimester CRL, BPD, and NT measurements. These findings support the hypothesis that physiological variation in BW can be reflected by variation in first-trimester fetal measurements. On croit depuis longtemps que la variation physiologique dans le poids fœtal se manifeste pendant la deuxième moitié de la grossesse; or, d'après des études récentes, une longueur cranio-caudale (LCC) et une clarté nucale (CN) atypiques entre 11 et 14 semaines de gestation seraient associées à une croissance fœtale anormale. Les résultats sur le sujet ont toutefois été limités par le manque d'exactitude de la datation pour les grossesses spontanées. Nous avons donc cherché à déterminer s'il existait une corrélation entre ces mesures et le poids à la naissance d'un bébé né à terme ou le rapport avec le poids attendu dans une cohorte de grossesses obtenues par FIV, pour lesquelles nous connaissions la date de conception exacte. Cette étude de cohorte rétrospective portait sur 227 grossesses uniques obtenues par FIV et menées à terme. Nous avons retenu les cas où la patiente avait subi une échographie au début du premier trimestre, puis une évaluation de la clarté nucale. La différence entre les valeurs mesurées et attendues pour la LCC, le diamètre bipariétal (DBP) et la CN a été calculée et corrélée avec le poids à la naissance réel ou le rapport avec le poids attendu. Le rapport a été calculé à l'aide du poids à la naissance et du poids attendu pour l'âge gestationnel. La différence entre les valeurs mesurées et attendues pour la LCC et pour le DBP à l'évaluation de la CN à la moitié du premier trimestre était corrélée avec le rapport avec le poids attendu à la naissance (rSpearman = 0,15; P = 0,023 et rSpearman = 0,27; P < 0,001, respectivement). Les mesures absolues et les rangs centiles de la CN (ajustés pour la LCC) étaient corrélés avec le rapport avec le poids attendu (rSpearman = 0,18; P = 0,005 et rSpearman = 0,14; P = 0,038, respectivement). Dans cette population de grossesses obtenues par FIV dont la date de conception était connue avec exactitude, nous avons observé une corrélation significative entre le rapport avec le poids attendu et la LCC, le DBP et la CN au premier trimestre. Ces constatations semblent confirmer l'hypothèse selon laquelle les mesures fœtales au premier trimestre peuvent laisser présager une variation physiologique du poids à la naissance.